Model Kolaboratif Pemerintah, Masyarakat, dan Sektor Swasta dalam Mengintegrasikan Tujuan SDGs ke dalam Rencana Pembangunan Daerah - Arif Rahman Hakim; Genius Umar (Journal of Current Research in Management, Policy, and Social Studies, 2025)
his study examines the collaborative model between government, community, and private sector in integrating the Development Goals (SDGs) into regional development plans. This collaboration is to ensure that development at the regional level can run and is in line with the achievement of SDGs. This study identifies the challenges and obstacles faced by each party in the collaboration process, as well as the factors that support the success of the collaboration. The results of the study indicate that commitment, transparency, and active community participation are key factors influencing the success of collaboration. In addition, information and communication technology also plays a role in facilitating effective collaboration. Based on these findings, it is recommended that government policies be more supportive of the private sector, increase community participation, and utilize technology to improve the efficiency and effectiveness of collaboration in achieving SDGs at the regional level.